Atypical pathological presentation of S. Suis serotype 2 induced cerebral abscess in a naturally infected buffalo calf (Indian Journal of Veterinary Pathology, 2025)
The present study reports a rare case of cerebral abscess in a 10 month old male crossbred buffalo calf showing the clinical signs of lateral recumbency, torticollis, stiffness of neck, muscle twitching, paddling movement and opisthotunus. Grossly, the brain showed a large abscess in anterior part of the right cerebral hemisphere. Histopathologically, purulent meningitis was observed showing marked infiltration of inflammatory cells in the leptomeningeal space. The brain parenchyma showed purulent exudates lined by thick connective tissue capsule, marked perivascular cuffing, multi-focal areas of gliosis, vasculitis and neuronal degenerations. The DNA from the affected brain tissue showed the presence of S. suis by PCR targeting gdh gene and further confirmed as serotype 2 by multiplex PCR amplifying 498 bp base pair fragment of the capsular gene. Immunohistochemically, the inflammatory cells infiltrating the brain parenchyma and glial cells showed the abundant immunoreactivity for SS2 antigens confirming the etiology. The histopathological, immunohistochemical and molecular findings support the diagnosis of rare case of S. suis serotype 2 induced cerebral abscess in a buffalo calf.